Marine Mammals Inhabiting the Baffin Bay North Water in Winter - Finley, Kerwin J.; Renaud, Wayne E. (ARCTIC, 1980)
Aerial surveys in March-April 1978 and March 1979 showed that some species of marine mammals overwinter in isolated areas of open water in the North Water in northern Baffin Bay. About 700 walruses and 37 bearded seals were seen, most over deep water (200-500 m) near SE Ellesmere Island in March 1979. Both species were much less common in 1978. Approximately 500 belugas were found in recurrent leads along the edge of the fast-ice in eastern Jones and Lancaster sounds and, to a lesser extent, in Smith Sound. Only 12 narwhals were seen. It has been concluded that the North Water is not a major overwintering area for marine mammals.